Processing and storage effects on anthocyanin composition and antioxidant activity of jams produced with Camarosa strawberry - Luis F Amaro (2013)
Anthocyanin profiles and radical scavenging activity of Camarosa strawberry jams as affected by two processing methods (conventional/industrial) and storage conditions were evaluated. Industrial strawberry jam produced in a closed system with vacuum preserved the anthocyanin composition (the total content was 35.77 +/- 2.56mg per 100g) when compared with conventional jam produced in an open system (3.35 +/- 0.05mg per 100g). However, the radical scavenging activity of conventional jam was lower than that of industrial jam, as EC50 was 52.99 +/- 0.94 and 44.33 +/- 2.47mgmL(-1), respectively. Two-way analysis of variance indicated a significant effect of processing method and storage time during 60days and a significant interaction for all variables except for EC50. Long-time storage of industrial jams at -8 degrees C leads to 80% reduction in anthocyanin content without loss of sensorial characteristics, whereas at room temperature the reduction was 98%, and the red colour was replaced by a brownish. Regardless of storage temperature, the radical scavenging activity of jams decreased 50-60% of its initial value.